1991
DOI: 10.1002/gcc.2870030611
|View full text |Cite
|
Sign up to set email alerts
|

Variant Translocations of Chromosome 13 in Alveolar Rhabdomyosarcoma

Abstract: In three cases of alveolar rhabdomyosarcoma with variant translocations, two tumors contained an identical translocation, t(1;13)(p36.1;q14); the third tumor contained a t(8;13)(p21;q14). All three patients were 2 years old, markedly younger than the median age for patients with t(2;13)-positive alveolar rhabdomyosarcoma. The alteration of genetic material on chromosome 13 may be of primary importance in the development of alveolar rhabdomyosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 3 publications
0
26
0
Order By: Relevance
“…The most prevalent ®nding in ARMS is a translocation, t(2;13)(q35-37;q14), which was detected in 70% of ARMS cases (Douglass et al, 1987;Turc-Carel et al, 1986;Wang-Wuu et al, 1988) (Figure 1). In addition, a variant translocation, t(1;13)(p36;q14), was identi®ed in a smaller subset of ARMS cases (Biegel et al, 1991;Oncogene (2001) 20, 5736 ± 5746 ã 2001 Nature Publishing Group All rights reserved 0950 ± 9232/01 $15.00 www.nature.com/onc *Correspondence: FG Barr; E-mail: barrfg@mail.med.upenn.edu Douglass et al, 1991). The 2;13 and 1;13 translocations have not been detected in any other tumor type and appear to be speci®c and sensitive markers of ARMS.…”
mentioning
confidence: 99%
“…The most prevalent ®nding in ARMS is a translocation, t(2;13)(q35-37;q14), which was detected in 70% of ARMS cases (Douglass et al, 1987;Turc-Carel et al, 1986;Wang-Wuu et al, 1988) (Figure 1). In addition, a variant translocation, t(1;13)(p36;q14), was identi®ed in a smaller subset of ARMS cases (Biegel et al, 1991;Oncogene (2001) 20, 5736 ± 5746 ã 2001 Nature Publishing Group All rights reserved 0950 ± 9232/01 $15.00 www.nature.com/onc *Correspondence: FG Barr; E-mail: barrfg@mail.med.upenn.edu Douglass et al, 1991). The 2;13 and 1;13 translocations have not been detected in any other tumor type and appear to be speci®c and sensitive markers of ARMS.…”
mentioning
confidence: 99%
“…Therefore, it was suggested that these abnormalities, taken together, might have a significant role in the genesis of the tumor (Magnani et al, 1991). The occurrence of a t(1;13)(p36;q14) is not an uncommon finding in RMS (Biegel et al, 1991;Douglass et al, 1991). It has been described that this translocation results in the formation of a chimeric protein consisting of part of the PAX7 gene on chromosome 1 and the FOXO1A (FKHR) gene on chromosome 13 (Davis et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Two cases of solid A-RMS have also been described with a t(2;13) (Parham et al, 1994). A minority of cases contain variants of this translocation; the most common being a t(1;13)(p36.1;q14) (Biegel et al, 1991;Dal Cin et al, 1991;Douglass et al, 1991;Whang-Peng et al, 1992). A study correlating karyotype with clinical characteristics determined that patients with a t(2;13) were older and that the tumors were located in the trunk (Douglass et al, 1993).…”
Section: Embryonal Rms (E-rms) Alveolar Rms (A-rms) and Pleomorphic mentioning
confidence: 99%